Dietary restriction as a fasting mimetic in aged mice: metabolic, cognitive, and neuroinflammatory evaluation - Gregosa, Amal (2021)
Aging is a physiological process that involves cognitive decline, decreased autophagic flux, and increased oxidative stress. Dietary restriction is a multitarget strategy that has been linked to several benefits, inducing autophagy flux, decreasing oxidative stress and inflammation, and improving metabolism. These effects establish dietary restriction as a possible approach to delay physiological aging and to prevent or treat aging-related diseases. In a previous work, we evaluated a protocol of periodic dietary restriction (PDR) in an animal model of familial Alzheimer’s disease. Now, we have studied the effects of this strategy on aged female mice (16 month-old), evaluating metabolic, cognitive, and neuroinflammatory changes. PDR involved 5 days of dietary restriction (DR) alternated with 9 days of ad libitum (AL) food intake for 7 weeks. During the DR period, mice ate 60% of their habitual intake. Animals under PDR showed similar body weight and glycemia to AL mice. During DR periods, circulating ketone bodies increased (1WAnova-Sidak, basal vs DR p<0.001) suggesting a fasting-like effect. Additionally, we evaluated cognitive performance by the novel object location recognition test. No changes were observed between AL and DR animals, but both groups’ performance was worse than that of 5 month-old mice, evidencing an age-related cognitive decline. We assayed S100b/GFAP by immunofluorescence in the hippocampus and analyzed morphological astrocytic parameters. S100b, an astrocytic pro-inflammatory marker, was diminished in DR mice (vs AL). However, GFAP immunoreactivity was unchanged. These preliminary results evidenced fasting-like effects in mice exposed to DR. Further, cognitive impairment in aged mice was corroborated, and a possible modulation of the pro-inflammatory S100b with DR. Future perspectives point to evaluating glial morphology in depth, and autophagy as a possible main mechanism for DR.